Identification of Land Subsidence Zone Distribution Using Ground Penetrating Radar Integrated with Cone Penetration Test: A Case Study of Maritime Museum and Syahbandar Tower, North Jakarta - Rahim, Rizka Aulia Shakila; Triana, Alya Ayu; Irawati, Selvi Misnia; Ruchimat, Acep (Universitas Islam Negeri Ar-Raniry, 2027)
and subsidence is a serious environmental issue in the coastal area of North Jakarta, particularly in Penjaringan District, where the historic buildings of the Maritime Museum and Syahbandar Tower are located. Identification of subsurface conditions regarding the distribution of subsidence zones is necessary to prevent structural damage that could result in significant losses. This study was conducted by integrating Ground Penetrating Radar (GPR) and cone penetration test (CPT). GPR measurements were performed using a GSSI SIR 4000 instrument at a frequency of 400 MHz, with a total of 8 survey lines and 2 CPT points. The radargram results show downward sloping reflections indicating land subsidence beneath the surface. Land subsidence zones were detected at depths of 0 – 3 m at different distances, presumably caused by deformation and uneven compaction. A fill soil layer was detected at depths of 0 – 1.5 m. The correlation between GPR and CPT data confirms the presence of sandy clay with cone tip resistance values of qc = 10–20 kg/cm² at depths of 0–4 meters, indicating very low bearing capacity consistent with the land subsidence identified in the GPR data. The results of this method demonstrate that the integration of GPR and CPT data provides a comprehensive and reliable assessment of land subsidence vulnerability as a basis for mitigation planning and sustainable development in the Jakarta area. Accordingly, this study bears significant relevance to the fields of applied physics and geophysics.